2023
DOI: 10.3389/fimmu.2023.1160710
|View full text |Cite
|
Sign up to set email alerts
|

High loading-dose of dupilumab resulted in rapid disease control in pediatric patients with atopic dermatitis

Abstract: BackgroundThe real-world experience of dupilumab in Chinese is limited, and the initial loading dose has not yet been deeply explored in patients aged <6 years.ObjectiveTo explore the efficacy and safety of dupilumab in Chinese patients with moderate-to-severe atopic dermatitis and investigate the effect of higher loading dose for disease control in patients aged <6 years.MethodsA total of 155 patients were divided into three groups according to age: <6 years, 6-11 years, and >11 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
(52 reference statements)
1
3
0
Order By: Relevance
“…Real-world research and phase III clinical trials have shown that, compared to the placebo group, dupilumab significantly improved NRS scores and Quality of Life (QoL)-related scores. 30–32 , 36 , 52–54 In addition, pediatric patients treated with dupilumab had good adherence and dosing persistence, which is consistent with adult results. In the 52-week open-label extension study (LIBERTY AD PED-OLE), patient adherence and medication persistence were good, with 253 of 294 patients continuing to be treated and only 11 patients dropping out of the trial due to lack of efficacy.…”
Section: Efficacy and Safety Of Dupilumabsupporting
confidence: 76%
See 1 more Smart Citation
“…Real-world research and phase III clinical trials have shown that, compared to the placebo group, dupilumab significantly improved NRS scores and Quality of Life (QoL)-related scores. 30–32 , 36 , 52–54 In addition, pediatric patients treated with dupilumab had good adherence and dosing persistence, which is consistent with adult results. In the 52-week open-label extension study (LIBERTY AD PED-OLE), patient adherence and medication persistence were good, with 253 of 294 patients continuing to be treated and only 11 patients dropping out of the trial due to lack of efficacy.…”
Section: Efficacy and Safety Of Dupilumabsupporting
confidence: 76%
“…The researchers speculated that this may be related to loading dose/ weight. 36,37 Long-term efficacy of dupilumab was also confirmed in real-world studies. In a multicentre, retrospective real-world study, a total of 91 patients aged 6-11 years completed 52 weeks of treatment, and compared to baseline, patients showed significant decreases in EASI scores, CDLQI scores, and NRS scores, in addition to the proportion of patients who achieved EASI50, EASI-75, and EASI-90, which was 95.6%, 86.8%, and 42.9%, respectively.…”
mentioning
confidence: 68%
“…A Chinese real‐world experience studied the efficacy and safety of a 16‐week dupilumab course (using also high loading doses) in 155 children 72 . The study classified children into three age groups (<6, 6–11, and >11 years).…”
Section: Recent Real‐world Studiesmentioning
confidence: 99%
“…Nonetheless, approved biologic therapies such as dupilumab may not suffice for all patients [ 6 ]. Recent research indicates that overweight and obesity may predict a suboptimal response to dupilumab treatment [ 7 , 8 ]. Adipokines hold potential as novel, precise therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%